(untitled) (ENTHYMEMA, 2019)
The psychoanalytic practice of the word finds its own regime in an affinity with the saying of poetry, made up of resonances rather than meaning and narration, evocative more of figures than of meaning. A poetess like Nadia Campana, at the intersection of the experience of psychoanalysis, barely touched, and that of the poetic vision, in which she immersed herself up to being overwhelmed, offers a starting point for a reflection that accompanies us in that extreme edge where enjoyment is presented in its aspect of destruction.